Corrosion Inhibition Effect of Acidic Extract of Bark of Eucalyptus Globulus on Mild Steel - Gupta, Dipak Kumar; Awasthi, Laxmi; Das, Anju Kumari; Yadav, Brahamdeo; Ghimire, Anita; Yadav, Amar Prasad (Tribhuvan University Journal, 2020)
The corrosion inhibition properties of the acidic extract of Eucalyptus globulus (EG) was investigated for mild steel (MS) using the weight loss method and open circuit potential (OCP) measurement. Corrosion inhibition of MS in 0.1M HCl was studied in the absence and presence of various concentrations of the acidic extract of EG barks. The results showed an increase in corrosion inhibition with increasing concentration of the extract. The inhibition efficiency of 100% EG extract was approximately 98.0% after 24 hours immersion in the acidic solution. FTIR spectrum showed the presence of compounds containing oxygen and nitrogen functional groups responsible for forming barrier layers onto MS surface. Open circuit potential (OCP) measurements showed that the EG extract acts as a mixed type inhibitor.